How the hydraulic characteristics of the process water clarification lightbox with suspended sediment in technological reliability - Смирнов, Ю.О.; Українець, М.О.; Сокольник, В.І. (Proceedings of National Aviation University (archive), 2008)
In this work are presented the results of research of connection of speed of ascending stream of water resulted in the area of defecation, speed of water on an exit from openings of distributive collector, and also speed of water movement in the drains receiver windows of clarifier with technological reliability of their work.